Reconstituted sorghum grain for finishing swine - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Gains of finishing pigs fed whole or rolled reconstituted sorghum grain (30% moisture) from 100 lbs. to an average of 210 lbs. were similar and similar to gains by pigs fed a ground sorghum grain ration. Compared on a 90% dry matter basis, pigs fed the ground ration were 7% more efficient than pigs fed the whole or reconstituted grain rations. Rolling the reconstituted sorghum grain improved feed efficiency (8%) and improved rate of gain as compared to the performance of pigs fed the whole reconstituted grain.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; Sorghum grain; Finshing pigs; Rate of gain; Performance